GEOCHEMICAL MAPPING BASED ON REGULARLY SPACED COMPOSITE STREAM SEDIMENT SAMPLES PRODUCED FROM STORED ALIQUOTS - STATE OF PARANÁ PRE-CAMBRIAN SHIELD, BRAZIL - Crisigiovanni, Fabio Luigi; Licht, Otavio Augusto Boni; Ferrari, Viviane Carillo; Porto, Claudio Gerheim (Geochimica Brasiliensis, 2019)
A collection of 6,587 active stream sediment samples covering about 4,800 km² in the Paraná Shield, southern Brazil was used to produce 75 composite samples each representing a 5’ x 5’ cell. The original samples were retrieved from the archives of the Geological Service of Paraná - MINEROPAR and the Geological Service of Brazil - SGB / CPRM. The composite samples were submitted to four analytical methods with the determination of 66 elements. Geochemical maps of the isolated elements along with bivariate correlation analysis showed six associations between elements, each representing specific lithologies and at least one area with high exploratory potential, which was previously unknown given the small amount of elements analyzed in the original samples. The geochemical maps were produced either by cell classification (pixel maps) or by the application of the minimum curvature interpolation method, considered as the best interpolator for the generation of the isograd maps (vector maps). The comparison between composite and original samples showed that, even with different analytical techniques, the element contents of the composite samples are similar to the average of the contents in the original samples on each cell. The results obtained allow us to recommend the adoption of this set of procedures in stream sediment sample collections covering large areas, with at least three advantages of: (a) eliminating field costs by retrieving already collected and archived samples, (b) reducing the amount of samples to be analyzed and (c) minimize any positioning errors of sampling sites collected before the advent of GPS equipment. The verification and detailing of the areas of interest evidenced by this procedure can be done easily with the analysis of the original samples still stored in the collections.